2022
DOI: 10.5551/jat.63249
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Distribution of Ceramides and Sphingosine among Lipoprotein and Lipoprotein-Depleted Fractions in Patients with Type 2 Diabetes Mellitus

Abstract: In addition to the quantity and quality, the carriers, such as lipoproteins and albumin, can affect the physiological properties and clinical significance of lipids. This study aimed to elucidate the modulation of the levels of ceramides and sphingosine, which are considered as proatherosclerotic lipids, in lipoproteins and lipoprotein-depleted fractions in subjects with type 2 diabetes. Methods:We separated the serum samples collected from healthy subjects (n = 22) and subjects with type 2 diabetes (n=39) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Sphingosine, an important member of sphingolipids, is a ubiquitous component of the cell membrane and serves a pivotal role in cell growth, metabolism regulation, signal transduction, and various physiological function ( Gaggini et al, 2022 ; Grewe et al, 2022 ). Previous publications demonstrated that sphingosine and sphingosine-1-phosphate (its downstream product) were bioactive biomolecules which exerted proinflammatory effects and promoted proapoptotic properties in the vascular endothelial cell, contributing to the occurrence and development of cardiovascular diseases ( Bernacchioni et al, 2022 ; Kurano et al, 2022 ). In recent studies, sphingosine levels were proven to be shifted in the inner tissues and perilymph and aggravated the oxidative stress and inflammation in sensorineural hearing loss and ototoxicity ( Romero-Guevara et al, 2015 ; Cencetti et al, 2019 ; Wang et al, 2020 ; Ramkumar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine, an important member of sphingolipids, is a ubiquitous component of the cell membrane and serves a pivotal role in cell growth, metabolism regulation, signal transduction, and various physiological function ( Gaggini et al, 2022 ; Grewe et al, 2022 ). Previous publications demonstrated that sphingosine and sphingosine-1-phosphate (its downstream product) were bioactive biomolecules which exerted proinflammatory effects and promoted proapoptotic properties in the vascular endothelial cell, contributing to the occurrence and development of cardiovascular diseases ( Bernacchioni et al, 2022 ; Kurano et al, 2022 ). In recent studies, sphingosine levels were proven to be shifted in the inner tissues and perilymph and aggravated the oxidative stress and inflammation in sensorineural hearing loss and ototoxicity ( Romero-Guevara et al, 2015 ; Cencetti et al, 2019 ; Wang et al, 2020 ; Ramkumar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is an inevitable and important question and deserves further investigation. Kurano et al found that Cer(18:1) behaves a differently from other ceramides in the HDL of patients with diabetes 8) . It is reasonable to speculate that each ceramide affects metabolism differently depending on…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In this issue of Journal of Atherosclerosis and Thrombosis, Kurano et al reported that they measured ceramides and sphingosine, including dihydrosphingosine, a molecule that is closely related to sphingosine (Fig. 1), in each serum lipoprotein and lipoprotein-deleted fraction of healthy controls and patients with diabetes and compared the distribution of these sphingolipids between the two populations 8) . Some of their patients with type 2 diabetic mellitus had complications related to cardiovascular diseases and diabetic nephropathy.…”
Section: See Article Vol 29: 1727-1758mentioning
confidence: 99%
See 2 more Smart Citations